Synthesis and activity evaluation of short antifreeze peptides of type I shorthorn sculpin antifreeze protein - Suliman Warrad, Ahmad Omar Abdelazim (2013)
Organisms living in cold environments are adapted to tolerate the freezing cold conditions and survive at subzero temperature by evolving antifreeze proteins (AFPs). AFPs bind to ice crystals and inhibit ice crystals growth and change their morphology. AFPs have function to depress the freezing point in non-colligative manner, resulting in a difference between the freezing point and the melting point of these organisms’ aqueous fluids, a property known as thermal hysteresis (TH). They are also capable of inhibiting ice recrystallization in the frozen state. This phenomenon called ice recrystallization inhibition (IRI). The main aim of this study is to synthesize short antifreeze peptides from shorthorn sculpin antifreeze protein and analyze the functional properties of these peptides. The analysis of the antifreeze activity of the short peptides was studied in order to investigate the role of each segment in the overall antifreeze activity of shorthorn sculpin AFP. The peptides were designed based on shortening the parent peptide into three fragments which represent different regions of shorthorn sculpin AFP. The synthesis of these peptides was performed following solid phase peptide synthesis method. The antifreeze activity of each peptide was determined experimentally by performing TH and IRI activity assay. The secondary structure of the short antifreeze peptides was determined by circular dichroism spectroscopy. Using solid phase peptide synthesis method yielded peptides with at least 68% purity. Antifreeze activity assay revealed that the three peptide fragments were devoid of TH activity. Peptides SC1 and SC2 demonstrated moderate IRI and ice structuring morphology activities, while SC3 showed no activity. Secondary structure analysis indicated that the helical content was reduced with increasing temperature. The results indicated that there is no correlation between the helical content and antifreeze activity of the short peptides. As a conclusion, synthesizing short peptide fragments based on shortening shorthorn sculpin antifreeze protein (SS3) would results in short peptide segments that behave as ice modifiers rather than efficient ice inhibitors or true antifreeze peptides.